Silica Sol-Gel Entrapment of the Enzyme Chloroperoxidase - Tuan Le; Selina Chan; Bassem Ebaid; Monika Sommerhalter (Journal of Nanotechnology)
The enzyme chloroperoxidase (CPO) was immobilized in silica sol-gel beads prepared from tetramethoxysilane. The average pore diameter of the silica host structure (~3 nm) was smaller than the globular CPO diameter (~6 nm) and the enzyme remained entrapped after sol-gel maturation. The catalytic performance of the entrapped enzyme was assessed via the pyrogallol peroxidation reaction. Sol-gel beads loaded with 4 μg CPO per mL sol solution reached 9–12% relative activity compared to free CPO in solution. Enzyme kinetic analysis revealed a decrease in kcat but no changes in KM or KI. Product release or enzyme damage might thus limit catalytic performance. Yet circular dichroism and visible absorption spectra of transparent CPO sol-gel sheets did not indicate enzyme damage. Activity decline due to methanol exposure was shown to be reversible in solution. To improve catalytic performance the sol-gel protocol was modified. The incorporation of 5, 20, or 40% methyltrimethoxysilane resulted in more brittle sol-gel beads but the catalytic performance increased to 14% relative to free CPO in solution. The use of more acidic casting buffers (pH 4.5 or 5.5 instead of 6.5) resulted in a more porous silica host reaching up to 18% relative activity.